1985
DOI: 10.1104/pp.77.4.795
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear, Virescent Mutants of Zea mays L. with High Levels of Chlorophyll (a/b) Light-Harvesting Complex during Thylakoid Assembly

Abstract: We have found nuclear, recessive mutants in Zea mays L where assembly of the major chlorophyll (a/b) light-harvesting complex (LHC) was not delayed relative to most other thylakoid protein complexes during thylakoid biogenesis. This contrasts with the normal development of maize chloroplasts (NR Baker, R Leech 1977 Plant Physiol 60: 640-644). All four mutants examined were allelic and virescent, and displayed visibly higher yields of leaf Chl fluorescence during greening. Fully greened mutants had normal lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Virescence is quite prevalent in higher plants and has long fascinated plant biologists. Early work has identified virescent mutants from many plant species including maize, cotton, tobacco, peanut, and bean, and genetic analyses have shown that both nuclear and chloroplast mutations can be responsible for the virescent phenotype (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Virescence is quite prevalent in higher plants and has long fascinated plant biologists. Early work has identified virescent mutants from many plant species including maize, cotton, tobacco, peanut, and bean, and genetic analyses have shown that both nuclear and chloroplast mutations can be responsible for the virescent phenotype (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Kyle and Zalik (18) examined thylakoid proteins in the virescent barley and found that during greening ofetiolated mutant plants, greening-specific proteins (presumably including cab protein) appeared later in development than in the wild type. Polacco et al (22) analyzed the v424 nuclear virescent maize mutant and reported that thylakoid proteins coded for by the chloroplast genome were present in decreased amounts, while the amount of the nuclear-encoded cab protein was similar to that in the control strain. No thylakoid polypeptides were missing in the v-424 mutant.…”
mentioning
confidence: 99%